The impacts of academic stress on college students' problematic smartphone use and Internet gaming disorder under the background of neijuan: Hierarchical regressions with mediational analysis on escape and coping motives - Gu, Xiao; Mao, Eric (Zeqing) (Frontiers in Psychiatry, 2023)
With sluggish economic growth in the post-pandemic era, the phenomenon “neijuan” becomes increasingly severe in many Asian countries like China. Neijuan refers to a hypercompetitive social environment wherein individuals involuntarily get involved in inhumane work or study hours, resulting in a considerable amount of tension and stress. Previous pathology research has shown that stress can trigger the overuse of Internet-based devices and services, which can subsequently lead to problematic smartphone use (PSU) and Internet gaming disorder (IGD). Provided college students are generally deemed one of the groups most susceptible to neijuan, limited attention has been given to the stimuli and the resultant psychological and behavioral ill-beings. Our study examined the impacts of academic stress on Chinese college students’ PSU and IGD problems, with the inclusion of escape and coping motives as mediators. Based upon the results of hierarchical regressions and path analysis, we found that whereas academic stress increased IGD tendency mediated through escape and coping motives, excessive use of smartphone might have developed into a habitual behavior rather than effective escape and coping instruments. Demographic and academic characteristics, such as gender and whether studying at a prestigious institution, also exerted influences on college students’ IGD intensity.